The Effect of Direct and Indirect Written Corrective Feedback on Writing performance of Students in Intensive Course - pipit suci anggriani (Language-Edu, 2020)
The effect of direct and indirect written corrective feedback has long been debated among the teachers and researchers. The previous studies have also been conducted and found the different results that have not been settled. It still becomes a big question, therefore the researcher conducts the same study in the different level, in non-formal education. This study aims are to find out which written corrective feedback is more effective in improving writing performance of the students and to verify the previous studies about the effectiveness of both feedback. The design of this study is a true experimental research. 21 students in intensive course participated in this study. They were divided into two groups. 10 students in experimental group One were given direct written corrective feedback and 11 students in experimental group Two were given indirect written corrective feedback. In analyzing the data the researcher used Independent sample T-test. The findings revealed that the students who are given direct written corrective feedback achieve significantly better (p: .002) writing performance than the students who are given indirect written corrective feedback. It means direct written corrective feedback is more effective in improving writing performance than indirect written corrective feedback. Keywords: writing performance, direct feedback, indirect feedback.